Exploring Students’ Perspectives on the Integration of TikTok Storytelling in Project-Based Learning Classroom Junior High School - Sri Sulis Kurniawati; Yeny Prastiwi; Endang Fauziati (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2026)
This study explores students’ perspectives on the integration of TikTok storytelling in Project-Based Learning (PjBL) classrooms. The purpose of the research is to investigate how the use of TikTok as a digital storytelling platform influences students’ engagement, learning experiences, and perceived learning outcomes. A qualitative descriptive approach was employed, involving students who participated in project-based activities that required them to create and share storytelling videos using TikTok. Data were collected through questionnaires, classroom observations, and interviews, and were analyzed thematically. The findings indicate that the integration of TikTok storytelling in PBL promotes positive student engagement, enhances creativity, and increases motivation in the learning process. Students perceived improvements in their communication skills, particularly in speaking and storytelling abilities, as well as greater confidence in expressing ideas. Additionally, the platform’s accessibility and multimedia features supported collaborative learning and learning autonomy. However, some challenges were identified, including technical limitations and the need for clear instructional guidance. Overall, the study concludes that TikTok storytelling can serve as an effective and innovative learning medium when integrated thoughtfully into Project-Based Learning classrooms, contributing to meaningful and student-centered learning experiences.